The Implementation of Guided Discovery Learning Model Using Simple Tools - Alberto Yonathan Tangke Allo; Sri Rosepda Br. Sebayang (Kasuari: Physics Education Journal (KPEJ), 2018)
The purpose of this research was to observe the implementation of the Guided Discovery Learning (GDL) model using simple tools toward the students conceptual understanding of the lesson. GDL model was applied to all students enrolled in the Physics Experiments I class in the 2018/2019 academic year at the. Physics Education Program, Teaching and Education Faculty of Papua University. This research is pre-experimental research using one-shot case study with used assessment implementation GDL model consists of Syntax GDL model, the make simple tools, the make Student Worksheet (LKPD), students' concept understanding, and student perceptions. The results are, implementation GDL model with an average value of 88.7% in the excellent category, the assessment of simple tools designed by students during GDL learning obtained the results of with an average value of 91.8% in the excellent category, Student Worksheet (LKPD) with an average value of 89.7% in the excellent category, students' concept understanding during GDL learning with an average value of 66,7% in the good category, and student perceptions of GDL implementation using a simple tool with an average value of 92,43% in the excellent category.